2009
DOI: 10.1093/cercor/bhn245
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric Asymmetry of Auditory Evoked Fields Elicited by Spectral versus Temporal Stimulus Change

Abstract: The investigation of functional hemispheric asymmetries regarding auditory processing in the human brain still remains a challenge. Classical lesion and recent neuroimaging studies indicated that speech is dominantly processed in the left hemisphere, whereas music is dominantly processed in the right. However, recent studies demonstrated that the functional hemispheric asymmetries were not limited to the processing of highly cognitive sound signals like speech and music but rather originated from the basic neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 35 publications
4
46
0
Order By: Relevance
“…At present there is substantial evidence for the leftward lateralisation of activity for tasks associated with a short temporal integration window from a range of EEG, MEG, fMRI and PET studies (Belin et al, 1998;Brown and Nicholls, 1997;Jamison et al, 2006;Johnsrude et al, 1997;Liebenthal et al, 2005;Molfese, 1978;Nicholls, 1996;Nicholls et al, 2002;Okamoto et al, 2009;Poeppel et al, 1996;Zaehle et al, 2007;Zatorre and Belin, 2001;Zatorre et al, 1992). Studies demonstrating the rightward lateralisation of slow temporal processing, whilst increasing in number, are less numerous.…”
Section: Evidence For Hemispheric Asymmetries In Auditory Temporal Inmentioning
confidence: 99%
See 1 more Smart Citation
“…At present there is substantial evidence for the leftward lateralisation of activity for tasks associated with a short temporal integration window from a range of EEG, MEG, fMRI and PET studies (Belin et al, 1998;Brown and Nicholls, 1997;Jamison et al, 2006;Johnsrude et al, 1997;Liebenthal et al, 2005;Molfese, 1978;Nicholls, 1996;Nicholls et al, 2002;Okamoto et al, 2009;Poeppel et al, 1996;Zaehle et al, 2007;Zatorre and Belin, 2001;Zatorre et al, 1992). Studies demonstrating the rightward lateralisation of slow temporal processing, whilst increasing in number, are less numerous.…”
Section: Evidence For Hemispheric Asymmetries In Auditory Temporal Inmentioning
confidence: 99%
“…The N1 is a widely studied measure of auditory signal processing in adults that has been used to examine hemispheric differences in auditory processing (Johnson et al, 2013;Näätänen and Picton, 1987;Okamoto et al, 2009;Poeppel et al, 1996). It is a negative deflection that occurs approximately 100 ms post-stimulus onset and is observed maximally at frontocentral sites (see Figs.…”
Section: Event-related Potential Indices Of Auditory Processingmentioning
confidence: 99%
“…Furthermore, functional cerebral asymmetries have been reported for processing such features (Okamoto et al, 2007;Zatorre and Belin, 2001). Using MEG, Okamoto et al (2009) investigated the time course of neural activity in response to auditory stimuli that differed in either spectral or temporal features. It was found that while processing spectral changes elicited greater activity in the right hemisphere, processing temporal change elicited greater activity in the left hemisphere.…”
mentioning
confidence: 99%
“…To fully understand why listening to Mozart's piano sonata can modulate functional cerebral asymmetries, future studies should manipulate several musical and acoustic factors systematically, and also include more standardised non-music audio material that is emotionally neutral (e.g., similar to those stimuli used by Okamoto et al, 2009). Moreover, future studies may include direct measures of arousal as well as mood assessments that are particularly sensitive in capturing between-as well as within-group differences.…”
mentioning
confidence: 99%
“…However, it has been noted by Binder et al (2000) and Mirz et al (1999) that both hemispheres do respond to nonverbal stimuli. In addition, it has been reported that the left hemisphere codes temporal-related information, and the right hemisphere codes spectral information (Liégeois-Chauvel, de Graaf, Laguitton, & Chauvel, 1999;Okamoto, Stracke, Draganova, & Pantev, 2009;Zatorre & Belin, 2001). Thus, it can be construed that in younger adults both hemispheres respond during temporal-resolution activities, responding to both spectral and temporal information.…”
Section: Discussionmentioning
confidence: 99%